Binding Property Evaluation of Low Melting Point Filaments with Conventional Filaments in Weft-Knitted Fabrics. Issue 2 (June 2018) - Lin, Qiaoqiao; Jiang, Jiali; Xu, Shuangxi; Chen, Yueping; Hu, Yuanchao; Wang, Xiuhua
In this paper, low melting point polyamide (LMPA) filaments and low melting point polyethylene terephthalate (LMPET) filaments were blended with conventional filaments, including polyamide (PA), polyethylene terephthalate (PET) and polypropylene (PP), to prepare weft-knitted fabrics. The binding properties of low the melting point filaments in weft-knitted fabrics after heat treatment were investigated by testing mechanical properties and observing the morphology. The effect of heat treatment on the binding properties of the low melting point filaments is discussed. Tensile stress at small deformations and Young's moduli of all fabrics increased and then decreased with increasing heat treatment temperature or time. Thus, an optimal heat treatment process is obtained. LMPA/PA fabric shows better binding properties than LMPET/PET fabric. Both are better than other fabrics considered in this study. This could lead to commercial application of these fabrics.